2022
DOI: 10.3390/ijms23169001
|View full text |Cite
|
Sign up to set email alerts
|

miRNA in Ischemic Heart Disease and Its Potential as Biomarkers: A Comprehensive Review

Abstract: Ischemic heart disease (IHD) constitutes the leading global cause of mortality and morbidity. Although significant progress has been achieved in the diagnosis, treatment, and prognosis of IHD, more robust diagnostic biomarkers and therapeutic interventions are still needed to circumvent the increasing incidence of IHD. MicroRNAs (miRNAs) are critical regulators of cardiovascular function and are involved in various facets of cardiovascular biology. While the knowledge of the role of miRNAs in IHD as diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…miR-145-mediated antiatherosclerotic therapy has been reported before. , Compared with UTMD-mediated drug or inflammatory factors therapy, UTMD-mediated miRNA therapy provides a unique fine-tuning to more directly and efficiently target the biological pathways that drive AS. miR-145 can simultaneously bind to and inhibit multiple target genes (such as the VSMCs differentiation genes Acta2 and Myh11 , the angiogenic factor VEGFA , and the pro-inflammatory cytokine- IL-16), thereby providing a mechanism to synchronize the regulation of the entire gene network.…”
Section: Resultsmentioning
confidence: 99%
“…miR-145-mediated antiatherosclerotic therapy has been reported before. , Compared with UTMD-mediated drug or inflammatory factors therapy, UTMD-mediated miRNA therapy provides a unique fine-tuning to more directly and efficiently target the biological pathways that drive AS. miR-145 can simultaneously bind to and inhibit multiple target genes (such as the VSMCs differentiation genes Acta2 and Myh11 , the angiogenic factor VEGFA , and the pro-inflammatory cytokine- IL-16), thereby providing a mechanism to synchronize the regulation of the entire gene network.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that miRNAs play important roles in the occurrence and development of several diseases ( 31 , 32 ). The changes in miRNA levels associated with cardiovascular diseases have attracted attention since they have significant diagnostic values ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in miRNA playing a role in coronary artery syndromes and in their potential diagnosis and prognosis role illustrated by numerous studies and reviews that covered this issue: Kumric et al [ 137 ], Guo et al [ 138 ], Theofilis et al [ 139 ], and Kong et al [ 140 ]. Some new and interesting information may be added to these descriptive reviews.…”
Section: Circulating Biomarkers Of Vulnerable Plaquesmentioning
confidence: 99%